Why do people participate in grassroots sustainability initiatives? Different motives for different levels of involvement - Moser, Stephanie; Bader, Christoph (Frontiers in Sustainability, 2023)
Grassroots sustainability initiatives experiment with alternative ways of consumption and are promising agents for fostering pro-environmental behavior change. However, sustainability initiatives depend on high levels of volunteering and collective action. With the present research we aimed to better understand why people participate in sustainability initiatives and whether doing so is an expression of a broader set of pro-environmental behaviors. We tested the predictive importance of various motivational factors derived from grassroots innovation research, the theory of planned behavior, and theories on collective action, using data from a cross-sectional factorial survey of participants in several sustainability initiatives in Switzerland (N = 180). Our results revealed different motivational patterns depending on the level of involvement. The intention to use services and offers of sustainability initiatives (low level of involvement) was best explained by favorable attitudes toward participation and perceived behavioral control, while the intention to volunteer for such initiatives (high level of involvement) was additionally based on strong social identity and a high belief in participative efficacy. Our results also revealed that participation in sustainability initiatives concurs with those other private-sphere pro-environmental behaviors that are most similar to the initiatives' activities. We conclude from our results that the divergence in motivational factors between users and volunteers might pose a challenge to the success of sustainability initiatives and therefore deserves greater attention in future research.